One-Tube Nested Real-Time PCR Assay for Rapid Screening of Porcine Cytomegalovirus in Clinical Samples - Wang, Hye-young; Song, Joong Ki; Shin, Seongho; Choi, Ki Myung; Kim, Hyunil (Frontiers in Veterinary Science, 2020)
Porcine cytomegalovirus (PCMV) is a pathogen that must be removed from pigs for use as organ donors in xenotransplantation. Recently, it has been found that when donor pigs are infected with PCMV, a pig-to-non-human-primate xenotransplantation lower transplant survival by 2 to 3 times. Therefore, highly sensitive methods are needed to maintain designated pathogen free (DPF) pig and screen for xenografts. The purpose of this study was to evaluate the performance of commercially available method with one-tube nested real-time PCR assay to quickly detect PCMV infection in clinical samples and compare the results with those of sequence analysis. Molecular diagnostic methods were used to evaluate 127 samples, including tissues and blood samples from pigs suspected of PCMV infection. The detection rate for positive PCMV was 38.6% (n=49), 23.6% (n=30), and 12.6% (n=16) in one-tube nested real-time PCR, nested PCR, and conventional PCR methods, respectively. All PCMV-positive samples in conventional PCR or nested PCR methods were also positive in the one-tube nested real-time PCR assay. All the PCR products in the three methods were checked for amplification of PCMV gene by PCR and subsequent direct sequencing. The results of one-tube nested real-time PCR were found to be consistent with those of sequence analysis for all the samples and showed good agreement (κ=1). Our study found that the one-tube nested real-time PCR assay is more sensitive than the other two methods. This assay required approximately 1.5 hours for completion. Therefore, we concluded that one-tube nested real-time PCR assay is a fast and reliable method for the characterizing pathogen responsible for PCMV infection.